The Effect of Job Satisfaction and Employee Loyalty on Employee Performance at PT Gistex Textille Bandung (Case Study of Employee at PT Gistex Textille) - Ayi Muhiban; Rheza Rivalino Nurohmat (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine how much influence job satisfaction and employee loyalty have on employee performance at PT. Gistex Textile. The research method used is descriptive and associative method. The unit of analysis in this research is the employees of PT. Gistex Textile. Based on the results of sample calculations using saturated sampling techniques, 228 participants were obtained as research samples. Multiple linear regression analysis was also carried out using the following analysis technique t-test and F-test. Based on the results of the study, the independent variables (job satisfaction and employee loyalty) indicated that there were factors that influenced the dependent variable (employee performance) by 59.8%. The magnitude of the influence of the service quality variable on the intention to use is 39.7%, and the effect of consumer trust on the intention to use is 20.1%. The implication of this research is that companies must conduct further analysis to understand the reasons employees feel dissatisfied with career development opportunities in the company. As well as creating performance-based incentive programs by designing programs related to employee performance and contributions so as to provide additional motivation to try harder and contribute optimally to achieve predetermined targets